Porous anodic alumina on galvanically grown PtSi layer for application in template-assisted Si nanowire growth - Stavrinidou Eleni; Breza Katerina; Frangis Nikos; Michelakaki Irini; Nassiopoulou Androula (Nanoscale Research Letters, 2011)
Abstract We report on the fabrication and morphology/structural characterization of a porous anodic alumina (PAA)/PtSi nano-template for use as matrix in template-assisted Si nanowire growth on a Si substrate. The PtSi layer was formed by electroless deposition from an aqueous solution containing the metal salt and HF, while the PAA membrane by anodizing an Al film deposited on the PtSi layer. The morphology and structure of the PtSi layer and of the alumina membrane on top were studied by Scanning and High Resolution Transmission Electron Microscopies (SEM, HRTEM). Cross sectional HRTEM images combined with electron diffraction (ED) were used to characterize the different interfaces between Si, PtSi and porous anodic alumina.